1998
DOI: 10.1038/ng0598-98
|View full text |Cite
|
Sign up to set email alerts
|

Association of the INS VNTR with size at birth

Abstract: Size at birth is an important determinant of perinatal survival and has also been associated with the risk for cardiovascular disease and type 2 diabetes in adult life. Common genetic variation that regulates fetal growth could therefore influence perinatal survival and predispose to the development of adult disease. We have tested the insulin gene (INS) variable number of tandem repeats (VNTR) locus, which in Caucasians has two main allele sizes (class I and class III; ref. 3), as a functional candidate polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
85
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(96 citation statements)
references
References 17 publications
10
85
1
Order By: Relevance
“…Interestingly, the studies previously reporting associations between the class III allele and altered birthweight presented conflicting results. One study reported an association with increased birthweight (~250 g) when considering non-changers (subjects with a small change in weight standard deviation score from birth to one year of age) [12], whereas another study demonstrated an association with a decreased birthweight (~140 g) [13]. Moreover, a recent study also reported a lack of association between the class III allele and size at birth [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the studies previously reporting associations between the class III allele and altered birthweight presented conflicting results. One study reported an association with increased birthweight (~250 g) when considering non-changers (subjects with a small change in weight standard deviation score from birth to one year of age) [12], whereas another study demonstrated an association with a decreased birthweight (~140 g) [13]. Moreover, a recent study also reported a lack of association between the class III allele and size at birth [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, an association between the class III allele and impaired insulin secretion among healthy subjects has been reported [11]. Fourthly, variation of the INS-VNTR has been associated with increased and decreased birthweight [12,13]. And finally, it has been suggested, in a study of obese children [2], that variation of the INS-VNTR affects fasting serum insulin levels, while a recent study reported an effect of the class III allele on increased BMI and decreased insulin sensitivity in three Caucasian cohorts comprising a total of 1184 children and 1099 parents [3].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest hypothesis would then be an as yet unidentified single nucleotide polymorphism accounting for the weight variance observed. Many have considered the VNTR aetiological of various phenotypes, [10][11][12][13] but recently others, including the original groups, have come to question the evidence that the VNTR is an aetiological site. 23,24 The uncertainty of a conclusion of linear regression vs bimodal step obliges examination of a wider genomic region.…”
Section: Discussionmentioning
confidence: 99%
“…The INS promoter variable number tandem repeat (VNTR) class I/III genotype has been shown by others to associate with type I diabetes, 10 obesity, 11 polycystic ovary syndrome obesity 12 and growth in early life, 13 and at least for type I diabetes is aetiological. 10 The INS VNTR locus is 596 bp 5' to the INS start site, and arises from tandem repetition of a 14-15 bp oligonucleotide consensus sequence.…”
Section: Introductionmentioning
confidence: 99%
“…An association between the insulin gene VNTR and infant size at birth for a subset of the cohort has been published. 3,4 Studies on associations between various polymorphisms and childhood infection, 5 atopy, asthma, and with intermediate phenotypes related to diabetes and heart disease, are under way or planned.…”
Section: Introductionmentioning
confidence: 99%